Complete training for TriCaster 455 and 855 - Almed, Faraz; Safari eBooks ([S.l.] : Class on Demand, 2012)
"This training covers: TriCaster 455, TriCaster 855, TriCaster 450, TriCaster 850, TriCaster 450 EXTREME and TriCaster 850 EXTREME. If you're just starting out with the NewTek TriCaster 455 or 855 or if you're considering purchasing this unit, this training is for you. Go from novice to productive user as we walk you through hardware / software setup then get you up to speed using NewTek's latest portable powerhouse."--Resource description page.
Title from title screen.
Author name and publication information from resource description page (viewed June 10, 2013).
Presenter, Faraz Almed.
Keywords: Motion pictures -- Production and direction; Video recordings -- Production and direction; Television -- Production and direction; Electronic books